Educational Process In Preparing Students For Professional Activity - Urinov Uygun Abdullayevich; Norpulatova Gulbakhor Makhmudovna (Genius Journals, 2024)
The article explains that the pedagogical process mainly includes two active features, systematic approach to self-development of students and comprehensive development of personality. In modern conditions, the concept of "technology" acquires a new meaning in the theory and practice of pedagogy
Keywords: pedagogical technology; education; student